"Osler's phenomenon": misdiagnosing Cushing's syndrome. Issue 936 (11th November 2003) - De, P; Evans, L M; Scanlon, M F; Davies, J S
Abstract : The clinical manifestations of Cushing's syndrome can be quite variable and are frequently mistaken, with consequent delayed diagnosis and significant morbidity and mortality. Harvey Cushing described the typical signs and symptoms of Cushing's syndrome but unfortunately attributed the features to myxoedema. The first typical description of a patient with Cushing's syndrome was probably made by Sir William Osler in 1898. Thus delay or misdiagnosis with consequent high morbidity and mortality exemplifies the history of Cushing's syndrome. Four cases of Cushing's syndrome are described that were associated with deteriorating morbidity because of the considerable delay from first presentation to a secondary care physician to eventual diagnosis. The clinical diagnosis was delayed in all the four patients, although they had symptoms and signs that were missed by a number of primary and secondary care physicians. Trans-sphenoidal surgery resulted in biochemical cure as well as improvement in the accompanying co-morbidity. Although still rare, the prevalence of Cushing's syndrome is increasing. Increasing clinical awareness and the use of appropriate screening tests should facilitate earlier diagnosis with reduced morbidity and mortality. Although the syndrome is named after Harvey Cushing, Sir William Osler was probably the first to describe it. Therefore, in deference to Osler's contribution to Cushing's syndrome and the work of Harvey Cushing, it is suggested that to the list of the other eponymous conditions of Osler-Weber-Rendu and Osler's nodes, should be added the delay or misdiagnosis of Cushing's syndrome—"Osler's phenomenon".